1986
DOI: 10.1210/jcem-63-1-62
|View full text |Cite
|
Sign up to set email alerts
|

Glucoregulatory Function of Thyroid Hormones: Interaction with Insulin Depends on the Prevailing Glucose Concentration*

Abstract: The effect of elevated serum thyroid hormone concentrations on insulin-induced glucose metabolism was studied in healthy subjects before and after T4 administration (250 micrograms T4/day for 10-14 days). This treatment induced moderate hyperthyroidism (T4, 15.2 micrograms/dl; T3, 200 ng/dl). The following results were obtained. Insulin receptor binding to a 90% enriched monocyte fraction or to mitogen-stimulated cultured T lymphocytes was decreased by T4 administration, whereas insulin binding to erythrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Since the response of (or to) catecholamines may differ between the thyroid states, this might contribute to our results. In fact, the glycaemic response to epinephrine infusion was also reduced by hyperthyroidism [lo, 191. It should be mentioned that our data in moderate hyperthyroid miniature pigs differ from results obtained in thyrotoxic subjects, where hepatic and/or peripheral insulin resistance is frequently observed [24-261. Since an increased insulin sensitivity is also observed in moderately hyperthyroid man [4], the different results are most probably explained by the degree of hyperthyroidism, and are obviously not due to species specific effects of thyroid hormones. This leads us to the more general idea that near physiological effects of T3 differ from its pharmacological actions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the response of (or to) catecholamines may differ between the thyroid states, this might contribute to our results. In fact, the glycaemic response to epinephrine infusion was also reduced by hyperthyroidism [lo, 191. It should be mentioned that our data in moderate hyperthyroid miniature pigs differ from results obtained in thyrotoxic subjects, where hepatic and/or peripheral insulin resistance is frequently observed [24-261. Since an increased insulin sensitivity is also observed in moderately hyperthyroid man [4], the different results are most probably explained by the degree of hyperthyroidism, and are obviously not due to species specific effects of thyroid hormones. This leads us to the more general idea that near physiological effects of T3 differ from its pharmacological actions.…”
Section: Discussionmentioning
confidence: 92%
“…With respect to insulin we could show recently that moderate hyperthyroidism may increase hepatic as well as peripheral insulin sensitivity [3,4]. With respect to glucagon, its portal and peripheral levels are frequently elevated in clinical as well as experimental hyperthyroidism [5,6].…”
mentioning
confidence: 99%
“…32,33 Steady-state glucose disposal rate was calculated from the mean rate of exogenous glucose infusion during the last 30 min of the clamp, after glucose space correction (M-value (mg kg À1 min À1 )). Steady-state concentrations of serum insulin and plasma glucose (coefficient of variation (CV) 6.0 ± 3.1%) were assayed using the previously described methods.…”
Section: Hyperinsulinemic Euglycemic Clampmentioning
confidence: 99%
“…Moreover, using the regular euglycaemic hyperinsulinaemic clamp, it was demonstrated that there is an impairment in the insulin-induced suppression of glucose production in hyperthyroid patients [2,8]. At low insulin levels, insulinstimulated glucose disposal is usually unaffected [2,[8][9][10][11], whereas it has been reported to be decreased [2], unchanged [8,10,12,13] or even increased [9,11,14,15] at high insulin levels. Other researchers reported that thyroid hormones blunted the insulin-induced increases in the total distribution volume of the exchanging pool of glucose, possibly reflecting an acceleration of intracellular glucose degradation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the actions of thyroid hormones are strongly dose-dependent. In addition, the interaction with insulin action depends on the prevailing glucose concentration [9]. All studies have been performed in patients with clinical thyrotoxicosis and in thyroid hormone-treated healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%